Lower Platelet Reactivity Is Associated with Presentation of Unstable Coronary Artery Disease - Leunissen, Tesse C.; Gijsberts, Crystel M.; Wisman, Peter Paul; Huisman, Albert; Berg, Maarten Ten; Asselbergs, Folkert W.; Hoefer, Imo E.; Pasterkamp, Gerard; Moll, Frans L.; de Borst, Gert Jan; Roest, Mark (International Journal of Angiology, 2016)
In patients with acute coronary syndrome, high platelet reactivity (PR) is associated with an increased risk of secondary thrombotic events. However, in patients undergoing elective percutaneous coronary intervention (PCI), no association between high PR and outcome has been demonstrated. At present, the relation of PR and clinical symptoms is unknown.To examine the association of PR with clinical indication for diagnostic angiography (stable or unstable coronary artery disease [CAD]), taking into account the influence of P2Y12 inhibitors.A platelet function score (PFS) was determined in 195 patients by quantifying fibrinogen binding and P-selectin expression with flow cytometry. We evaluated the PFS with clinical presentation of stable or unstable CAD, angiographic severity of CAD, and the incidence of cardiovascular events during 2 years of follow-up. All data were analyzed stratified by P2Y12 inhibitor use (long-term and preprocedural versus none).Surprisingly, among non-P2Y12 inhibitor users, the PFS was lower in patients with unstable CAD compared with stable CAD (5.6 ± 1.8 vs. 7.4 ± 1.6; p = 0.001). Angiographic CAD severity showed no relation with PFS. The SYNTAX score tended to be inversely related with PFS: low PFS, 13.2 (IQR, 11.9–19.1); median PFS, 10.0 (IQR, 5.0–14.0); and high PFS, 8.0 (IQR, 5.0–13.0), without significance (p = 0.304). Patients with low PFSs required more re-PCIs than those with median and high PFSs (11.1 vs. 4.7 vs. 0.0%, p = 0.004). This association was modified for patients using P2Y12 inhibitors.Among patients without P2Y12 inhibitors undergoing coronary angiography, presentation of unstable CAD is independently associated with lower PR.
Keywords: P2Y12 inhibitor; platelet reactivity testing; coronary artery disease; coronary angiography; high on-treatment platelet reactivity; platelet function testing; flow cytometry